Authenticity as a compromise : a critical discourse analysis of Sámi tourism websites - de Bernardi, Cecilia (Journal of Heritage Tourism, 2019)
Authenticity is considered a very important means to attract tourists. Different enterprises and destinations compete for visitors and authenticity is an important factor for visitors’ travel decisions. Within the context of indigenous and cultural tourism, several studies have criticized the way in which indigenous and local populations are portrayed in order to attract tourists, since they often involve colonial images and descriptions that are no longer corresponding to the contemporary situation. This study presents an alternative perspective on the discussion on tourism marketing in relation to authenticity. Through critical discourse analysis and retroduction, this study has analysed the websites of Sámi tourism companies from Sweden. The discussion put forward in this study is not a generalizing picture of how the Sámi peoples choose to market themselves, but it problematizes how these particular enterprises relate to issues of authenticity in the representation of cultural heritage. This paper also presents a new approach to authenticity seen as a compromise. The results of this study present one side of a multifaceted discussion on the struggle between different discourses on representations and authenticity that are often the main channel to reach and attract potential visitors.